The Association Between Inflammaging and Age-Related Changes in the Ruminal and Fecal Microbiota Among Lactating Holstein Cows - Zhang, Guoxing; Wang, Yachun; Luo, Hanpeng; Qiu, Wenqing; Zhang, Hailiang; Hu, Lirong; Wang, Yajing; Dong, Ganghui; Guo, Gang (Frontiers in Microbiology, 2019)
Inflammaging is well understood in the study of humans; however it is rarely reported for dairy cows. To understand the changing pattern of the gut microbiota, inflammatory status and milk production performance during the aging process in cows, we grouped 180 cows according to their lactation period: L1 (n = 60, 1st lactation), L3 (n = 60, 3rd lactation), and L5+ (n = 60, at least 5th lactation) and analyzed their milk components and daily milk yields to evaluate the changing pattern of milk production. The microbiota was analyzed using high-throughput sequencing of amplicons of 16S rRNA, which also allowed us to predict the functions of microbes and then study the changing pattern of the ruminal and fecal microbiota. Serum cytokines were measured to study the progress of inflammaging in the cows. We found that old cows (L5+) suffered from a long-term and low-level chronic inflammation, as indicated by significantly higher levels of inflammatory cytokines IL-10, TNF-α, and TGF-β in the L5+ group (p < 0.001). We also observed a significant decrease in daily milk yield and milk lactose, as well as a significant increase in somatic cell score, among the cows in the L5+ group. For the gut microbiota, most of the genera belonging to Prevotellaceae and Lachnospiraceae, which had a higher abundance among cows of both the L1 and L3 groups (LEfSe, LDA > 2), showed a similar change pattern during the aging process, both in the rumen and in feces, and across the six farms. Beneficial bacteria, like Bacteroidaceae, Eubacterium, and Bifidobacterium, displayed lower abundance in the feces of the L5+ group (LEfSe, LDA>2). Reconstruction of the fecal bacteria community indicated transformation of the fermenting pattern of older cows’ (L5+) feces microbiota, with increased functions related the protein metabolism and fewer functions related to carbohydrate and lipid metabolism compared with those in L1 (p < 0.05). Finally, the connections among these changing patterns were revealed using redundancy analysis and network analysis. The results support the hypothesis of prolonging a cows’ productive life and improve dairy cow milk productive performances by manipulating the gut microbiota.